Utility of food pellets containing 1-aminobenzotriazole for longer term in vivo inhibition of cytochrome P450 in mice. (2nd January 2019) - Stringer, Rowan; Cordier, Valerie; Afatsawo, Catherine; Arabin, Philip; Desrayaud, Sandrine; Hoffmann, Laurent; Lehmann, Daniel; Lowe, Philip John; Risser, Francis; Thiel, Julia; Widmer, Toni; Wipfli, Peter; et al.
Abstract: 1. The utility of 1-aminobenzotriazole (ABT), incorporated in food, has been investigated as an approach for longer term inhibition of cytochrome P450 (P450) enzymes in mice. 2. In rats, ABT inhibits gastric emptying, to investigate this potential limitation in mice we examined the effect of ABT administration on the oral absorption of NVS-CRF38. Two hour prior oral treatment with 100 mg/kg ABT inhibited the oral absorption of NVS-CRF38, T max was 4 hours for ABT-treated mice compared to 0.5 hours in the control group. 3. A marked inhibition of hepatic P450 activity was observed in mice fed with ABT containing food pellets for 1 month. P450 activity, as measured by the oral clearance of antipyrine, was inhibited on day 3 (88% of control), week 2 (83% of control) and week 4 (80% of control). 4. T max values for antipyrine were comparable between ABT-treated mice and the control group, alleviating concerns about impaired gastric function. 5. Inclusion of ABT in food provides a minimally invasive and convenient approach to achieve longer term inhibition of P450 activity in mice. This model has the potential to enable pharmacological proof-of-concept studies for research compounds which are extensively metabolised by P450 enzymes.